Conflict between the Norn and Codification in the Period of Language Instability (a case Study of New Indeclinable Nouns of Russian Language): Конфликт нормы и кодификации в период языковой нестабильности (на материале новых несклоняемых существительных русского языка) - Marinova, Elena (Przegląd Wschodnioeuropejski, 2019)
The article deals with the characteristic feature of the period of language instability, namely the conflict between the norm and codification in one of the Russian language areas that is subject to greatest variation. The author analyses establishment of the new norm in the process of assigning grammatical category of gender to borrowed indeclinable nouns. The study of this lexical group shows that approximately half of the new words form gender according to the principle of semantic analogy. This fact allows us to maintain that in the Russian of the XXI c. there is a process of broadening in the sphere of application of the rule about assigning gender to indeclinable inanimate onyms and abbreviations. Previously having a limited sphere of application, now this rule also extends to indeclinable inanimate appellatives. However the action of the “older” norm, according to which indeclinable nouns were assigned neuter gender, is also manifested, creating conditions for word variation.